Degradation analysis of dynamic properties for plain concrete structures under mixed-mode fracture conditions via an improved cohesive crack approach - Umberto De Maio; Daniele Gaetano; Fabrizio Greco; Raimondo Luciano; Andrea Pranno (Fracture and Structural Integrity)
The present work investigates the crack-induced degradation of the dynamic characteristics in plain concrete elements subjected to mixed-mode fracture conditions. Specifically, a discrete fracture model, based on an inter-element cohesive approach, has been improved and implemented into a 2D finite element framework to evaluate the progressive variation of the static and dynamic properties as the damage level increases. The obtained numerical results highlight the effectiveness of the proposed model in determining the load-carrying capacity and the degradation of natural vibration frequencies during damage propagation, demonstrating its applicability in the framework of structural health monitoring